Genotypic and Phenotypic Resistance to Clarithromycin in Helicobacter pylori Strains - Gong, Eun Jeong (J Clin Med, 2020)
Background: The increasing prevalence of antimicrobial resistance, together with the lack of novel treatment options, negatively affects successful eradication of Helicobacter pylori. The aim of this study was to investigate genetic mutations in the 23S rRNA genes, which is associated with clarithromycin resistance, and to determine the clinical impact of genotype on phenotypic antimicrobial resistance. Methods: A total of 46 H. pylori strains were obtained from 13 patients, before and after unsuccessful eradication with clarithromycin-based triple therapy. The phenotypic resistance of each H. pylori strain was determined by minimum inhibitory concentration against clarithromycin using the serial two-fold agar dilution method. The genomic sequences of 23S rRNA genes were identified through next-generation sequencing, and nucleotide variants were determined based on comparison with genome sequences of the reference strain H. pylori 26695. Results: Clarithromycin resistance was found in 9 of 13 subjects before treatment and all subjects after unsuccessful eradication. Whole-genome sequencing of the 23S rRNA genes detected 42 mutations on 40 nonidentical loci, including 2147A>G (formerly 2143A>G) and 2146A>G (formerly 2142A>G). All strains with clarithromycin-resistant phenotype had either 2147A>G or 2146A>G mutation. When comparing genotype and phenotype for clarithromycin resistance, there was a significant association between 2147A>G mutation and clarithromycin-resistant phenotype. Conclusions: All clarithromycin-resistant strains had either 2146A>G or 2147A>G mutation, suggesting that tests targeting these two mutations may be enough for the prediction of clarithromycin resistance in this population.